Analysis of Achievements and Factors Playing a Role in Achieving Complete Basic Immunization During the Adaptation Period to the COVID-19 (Coronavirus Disease) Pandemic in Padang, Indonesia - Kartika, Putri Sri; Hardisman; Yuniar Lestari (Community Medicine and Education Journal, 2024)
The immunization program is a global program to prevent child deaths and provide immunity against infectious diseases. In Padang City, complete basic immunization coverage (IDL) in 2021 is still low (76.5%) compared to the target of 95%. This research aims to analyze the achievements of the IDL program in Padang City during the adaptation period to the COVID-19 pandemic. This research method is mixed methods research with a stratified random sampling technique. The results showed that the age frequency distribution of the baby's mothers was mostly 26-40 years old (83.2%), with a high level of education (78.4%) and more people working (52%). The frequency distribution of IDL status in Padang City shows an incomplete category of 67.2%. There is a significant relationship between the level of education, level of knowledge, attitudes and roles of health workers, and IDL status. The most dominant factor is the level of knowledge. IDL coverage is still low due to mothers' lack of understanding about the immunization schedule due to mothers' busy lives, family restrictions, and socio-cultural factors.